Stigma and quality of life in adults with sickle cell disease in Jamaica and the United States. Issue 5 (28th May 2023) - Bulgin, Dominique; Asnani, Monika; Vorderstrasse, Allison; Royal, Charmaine; Pan, Wei; Tanabe, Paula
ABSTRACT: Sickle cell disease (SCD) is the most common inherited blood disorder in both Jamaica and the United States and is characterized by poor quality of life and debilitating complications, with the hallmark symptom being pain caused by acute and chronic conditions. Individuals with SCD often experience stigma due to their disease status, opioid use, and race. This study sought to understand the influence of perceived stigma and demographic/clinical characteristics on quality of life in adults with SCD in Jamaica (n = 50) and the United States (n = 50). Participants completed interviewer-administered surveys including demographic/clinical characteristics; the Measure of Sickle Cell Stigma (MoSCS); and the Adult Sickle Cell Quality of Life Measurement System (ASCQ-Me). A set of general linear models for each country was built to examine the influence of explanatory variables on the quality of life outcomes. Overall, stigma scores were low for both countries, with the exception of the MoSCS disclosure concerns and expected discrimination subscales, where scores averaged medium and high, respectively. In both countries, being employed was associated with better quality of life; and reports of stigma (internalized stigma and expected discrimination) was associated with worse quality of life. These findings have several implications for healthcare providers caring for individuals with SCD, policy makers, and researchers. Specifically, findings can be used to advocate for improved access to mental health care for individuals with SCD and inform stigma reduction intervention approaches in SCD.